Childhood-Onset Disease Predicts Mortality in an Adult Cohort of Patients with Systemic Lupus Erythematosus - Hersh, Aimee O. (2010)
OBJECTIVE: To examine childhood-onset disease as a predictor of mortality in a cohort of adult patients with systemic lupus erythematosus (SLE). METHODS: Data were derived from the University of California Lupus Outcomes Study, a longitudinal cohort of 957 adult subjects with SLE that includes 98 subjects with childhood-onset SLE. Baseline and follow-up data were obtained via telephone interviews conducted between 2002-2007. The number of deaths during 5 years of follow-up was determined and standardized mortality ratios (SMRs) for the cohort, and across age groups, were calculated. Kaplan-Meier life table analysis was used to compare mortality rates between childhood (defined as SLE diagnosis <18 years) and adult-onset SLE. Multivariate Cox proportional hazard models were used to determine predictors of mortality. RESULTS: During the median follow-up period of 48 months, 72 deaths (7.5% of subjects) occurred, including 9 (12.5%) among those with childhood-onset SLE. The overall SMR was 2.5 (CI 2.0-3.2). In Kaplan-Meier survival analysis, after adjusting for age, childhood-onset subjects were at increased risk for mortality throughout the follow-up period (p<0.0001). In a multivariate model adjusting for age, disease duration and other covariates, childhood-onset SLE was independently associated with an increased mortality risk (hazard ratio [HR]: 3.1; 95% confidence interval [CI]: 1.3-7.3), as was low socioeconomic status measured by education (HR: 1.9; 95% CI 1.1-3.2) and end stage renal disease (HR: 2.1; 95% CI 1.1-4.0). CONCLUSION: Childhood-onset SLE was a strong predictor of mortality in this cohort. Interventions are needed to prevent early mortality in this population.